Sustainability Transition and 6G Mobile Communications - Matinmikko-Blue, Maria; Arslan, Ahmad (Springer, 2023)
This chapter aims to academically highlight the link between 6G mobile communications and the transition to sustainability. Using both theoretical arguments and practical examples, the current chapter applies a multi-level perspective (MLP) to the sustainability transition to highlight the specificities of niches, socio-technical regimes, and exogenous socio-technical landscapes of 6G technology in relation to the sustainability transition. Moreover, the current chapter is one of the rare studies that focuses on the larger picture in the 6G and sustainability debate by highlighting specific UN SDGs which can be achieved by the sustainability transition and the role of both endogenous and exogenous factors using an MLP lens. Finally, this chapter offers specific theoretical, practical, and policy implications.
Keywords: Sustainability; Sustainability transition; Resilience; 6G; Multi-level perspective; sustainable development